Mapping Research Trends in Materials-Based Science Education for Sustainable Development Goals: A Bibliometric Study - Fiandini, Meli; Nandiyanto, Asep Bayu Dani (Bumi Publikasi Nusantara, 2024)
This study maps research trends, knowledge structures, and thematic developments in materials-based science education within the framework of the Sustainable Development Goals (SDGs). A total of 467 documents from the Scopus database (2015-2024) were analyzed using a quantitative bibliometric approach with VOSviewer software. The analysis includes keyword co-occurrence, author collaboration, country contributions, and topic evolution. Results indicate a significant growth in publications since 2020, with authors like Nandiyanto and countries such as the United States being key contributors. Prominent keywords (sustainability, learning, application, and teaching material) highlight a dominant focus on pedagogical and sustainability issues. Overlay visualizations show a thematic shift from technical material issues to competency-based learning approaches. These findings underscore the need for science curricula and teaching strategies that incorporate sustainability principles and material innovation. The study offers a strategic reference point for researchers and educators to align science education with global sustainability challenges.